2010
DOI: 10.1007/s10620-010-1377-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-hepatic Insults Are Common Acute Precipitants in Patients with Acute on Chronic Liver Failure (ACLF)

Abstract: ACLF is a common problem in our clinical practice. Non-hepatic insults like non-hepatotropic infections/sepsis are common acute precipitating events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 20 publications
9
75
0
Order By: Relevance
“…The best prognostic score for hepatic group is iMELD and for extrahepatic group is CLIF-SOFA. Similar to our previous data, 7,8 in the present study, alcohol was the predominant cause of chronic liver disease, alcoholic hepatitis was the most common hepatic insult, and infection was the most common extrahepatic insult. This is in contrast to studies from East Asia where hepatitis B is the predominant cause of chronic liver disease as well as acute insult in patients with ACLF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The best prognostic score for hepatic group is iMELD and for extrahepatic group is CLIF-SOFA. Similar to our previous data, 7,8 in the present study, alcohol was the predominant cause of chronic liver disease, alcoholic hepatitis was the most common hepatic insult, and infection was the most common extrahepatic insult. This is in contrast to studies from East Asia where hepatitis B is the predominant cause of chronic liver disease as well as acute insult in patients with ACLF.…”
Section: Discussionsupporting
confidence: 92%
“…The APASL group considers only hepatic insults/injury as acute precipitating event, whereas EASL also includes extrahepatic insult such as the sepsis and upper gastrointestinal bleeding as a cause of acute insult. 2,[4][5][6][7] The chronic liver failure (CLIF) acute-on-chronic liver failure in cirrhosis (CANONIC) study has defined ACLF based on increased 28-day mortality in patients with liver cirrhosis and acute decompensation. In a previous study, we have demonstrated chronic liver failure-sequential organ failure assessment (CLIF-SOFA) criteria to be better than APASL criteria in defining ACLF.…”
mentioning
confidence: 99%
“…A minor acute insult may be enough to cause the ACLF in a patient with severe underlying chronic liver disease, and a severe acute insult may be required in a patient who has mild underlying chronic liver disease. 7,14 Both hepatic and non-hepatic insults could occur as acute precipitating events leading to the syndrome of ACLF. The 'hepatic' precipitating events, that directly exaggerate the liver injury, are alcoholic hepatitis, drug-induced liver injury, superimposed viral hepatitis, portal vein thrombosis and ischemic hepatitis.…”
Section: Concept Of Acute-on-chronic Liver Failurementioning
confidence: 99%
“…17 Subsequently, many publications have reported HEV as one of the leading causes for decompensation of cirrhosis from Asia and Africa, where HEV is endemic (Table 1). 14,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Most of these studies have used the APASL definition of ACLF and in median21% of cases (range 4-72%) of ACLF, HEV was the precipitating cause for liver decompensation. This contrasts with the Western countries where HEV is rarely the precipitating cause of acute decompensation in ACLF.…”
Section: Role Of Hepatitis E Virus In Acute-on-chronic Liver Failurementioning
confidence: 99%
“…6,7 ATT constitutes an important acute precipitating event in decompensation of underlying known or unknown liver disease in India. 8 There is paucity of data in defining hepatotoxicity in patients with cirrhosis and clear guidelines do not exist regarding the monitoring of such patients, modification of the antitubercular regimen and mode of reintroduction of individual antitubercular therapy. Little is known about the characteristics of TB in patients with liver cirrhosis.…”
mentioning
confidence: 99%